Epidemiology of traumatic spinal cord injury in Tianjin, China: An 18-year retrospective study of 735 cases. (2nd November 2019) - Li, Hai-Liang; Xu, Hong; Li, Yu-Lin; Sun, Shi-Wei; Song, Wen-Ye; Wu, Qiang; Ai, Jie; Sun, Jing-Cheng; Ning, Guang-Zhi; Feng, Shi-Qing
Abstract : Study Design: Hospital-based retrospective study Objectives: To evaluate the pathogenetic features of traumatic spinal cord injury (TSCI) during 1999–2016 according to changed injury etiology with time, explore different characteristics of patients suffered a TSCI during 1999–2007 and 2008–2016 in Tianjin, China. Setting: Tianjin Medical University General Hospital Methods: In this study, the medical records of TSCI patients were obtained from Tianjin Medical University General Hospital (TMUGH) from 1st January 1999 to 31th December 2016. Variables were recorded, including age, gender occupation, etiology, the level of injury, America Spinal Injury Association (ASIA) impairment scale, the severity, concomitant injuries, death and its cause. To explore the differences in characteristics by etiology and by two periods, related statistical methods were used to calculate the correlation of some variables. Differences in etiology of TSCI during 1999–2016 were evaluated and differences in epidemiological characteristics were separately compared and analyzed between the 1999–2007 period and the 2008–2016 period. Results: From 1999–2016, 831 TSCI cases were identified and 96 cases were excluded from analyses. The male-to-female ratio was 2.9:1 and the mean age was 49.7±15.2 years, which changed significantly between 1999–2007 (45.1±14.2) and 2008–2016 (51.6±15.2). Traffic accidents (45.8%) were the leading cause of TSCI during the 1999–2007 period, followed by low falls (30.7%). However, the opposite result was observed during the 2008–2016 period. Significant difference was observed compared with thoracic, lumbar and sacral levels, cervical level was the most commonly affected levels and the percentage decreased to a certain degree between 1999–2007 and 2008–2016 (from 84.4% to 68.9%). The proportions of ASIA grades A, B, C, and D were 20.5%, 10.3%, 23.3%, and 45.9%, respectively. The percentage of complete tetraplegia decreased from 22.9% in 1999–2007 to 13.2% in 2008–2016, and the percentage of incomplete paraplegia increased from 9.7% to 27.9%. Conclusion: According to the changes in the epidemiological characteristics of TSCI, relevant health service, laws and regulations, preventative strategies should be readjusted to follow up the changing situation and epidemiological characteristics of TSCI.